Knowledge, attitude and preventive practices related to sexually transmitted diseases among university students in Malaysia - Folasayo, Adigun Temiloluwa (2015)
Sexually Transmitted Diseases (STDs) are among the world’s most common cause of illness and they are a major health concern for young people around the world. STDs have become a global burden particularly to the health sector because they are deeply connected to human behavior and fundamental society problems. Knowledge about crucial aspects of STDs is very important to enable youths disengage from behaviors that may place them at risk of contracting STDs. Howbeit, being knowledgeable may not guarantee that practices related to the prevention of STDs such as correct/consistent condom use will be followed. This study was carried out in a bid to assess the level of knowledge, attitude and preventive practices related to STDs among university students in Malaysia. This cross-sectional study employed simple random sampling to select the target population. The sample size was 748. The data was collected between May and August, 2014 using modified, pretested, validated, self-administered questionnaires. The response rate was 94%. Data was analyzed using SPSS version 21. Out of the 700 students who took part in the study, majority of the students were females (63.6%) and the age distribution ranged from 17 to 30 with a mean (SD) of 22.14 (2.771). The main source of STDs information was the internet (77.3%). The overall mean (SD) knowledge score of the respondents was 24.13 (8.540). The mean (SD) attitude score was 14.02 (2.674). The mean (SD) practice score was 1.137 (0.994). Logistic regression showed that knowledge level of the respondents was influenced by the students’ age group (AOR=1.707, 95% CI=1.183-2.46, p=0.004) and preventive practice was influenced by religion (AOR= 1.416, 95% CI= 1.077-1.862, p= 0.013). Logistic regression further showed that attitude level was strongly influenced by the students’ knowledge level (AOR= 2.349, 95% CI= 1.733-3.181, p= 0.001). Conclusively, the study reveals a lot of gap and misconceptions in the level of knowledge of the students on STDs. Low level of condom use and having sex with multiple partners was reported among the students who had sex. There is a need to implement sustained STDs prevention intervention program that will provide correct, consistent and up to date knowledge on STDs and also emphasize translation of this knowledge into acceptable/safe sexual practice.